2019
DOI: 10.1097/rli.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hypersensitivity Reactions to Iopromide After Intra-Arterial Versus Intravenous Administration

Abstract: This edition of the ACR Manual on Contrast Media replaces all earlier editions. It is being published as a webbased document only so it can be updated as frequently as needed.This manual was developed by the ACR Committee on Drugs and Contrast Media of the ACR Commission on Quality and Safety as a guide for radiologists to enhance the safe and effective use of contrast media. The Committee offers this document to practicing radiologists as a consensus of scientific evidence and clinical experience concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 80 publications
1
19
0
3
Order By: Relevance
“…Реакции гиперчувствительности, также называемые «немедленными реакциями гиперчувствительности», «аллергическими реакциями», «аллергоподобными реакциями», «анафилактоидными реакциями», «идиосинкразическими реакциями», обычно не опосредованы иммуноглобулинами класса Е, потенциально очень тяжелы и могут быть даже смертельны [16].…”
Section: реакции гиперчувствительностиunclassified
See 2 more Smart Citations
“…Реакции гиперчувствительности, также называемые «немедленными реакциями гиперчувствительности», «аллергическими реакциями», «аллергоподобными реакциями», «анафилактоидными реакциями», «идиосинкразическими реакциями», обычно не опосредованы иммуноглобулинами класса Е, потенциально очень тяжелы и могут быть даже смертельны [16].…”
Section: реакции гиперчувствительностиunclassified
“…2.Comparing the signal intensity value when using standard and personalized (adjusted for body mass and scanning duration) computed tomography protocols with contrast enhancement [15] помочь в решении этой проблемы. Такой анализ для йопромида провели J. Endrikat et al [16]. При его использовании РГ развилась у 822 из 133 331 пациента (частота составила 0,2% и 0,7% при внутриартериальном и внутривенном введении йопромида соответственно).…”
Section: реакции гиперчувствительностиunclassified
See 1 more Smart Citation
“…In addition, ICM-induced AU has long been regarded as non-IgE-mediated pseudoallergic reaction involving direct complement activation ( 13 ), while accumulating evidence indicated that ICM-specific IgE-mediated AU (type I allergic reaction) may have been underreported in the past due to lack of pertinent allergy testing ( 14 , 15 ). Without regard to IgE levels, excessive histamine or other biogenic amines released by basophils and tryptase by mast cells are also a characteristic of immediate HSRs (including AU) to ICM, which were partially evidenced by antihistamine treatments and blood tests ( 9 ). However, another disputable aspect that prevention of immediate HSRs by premedication with corticosteroids or antihistamines remains uncertain still challenges the role of IgE-mediated allergy in AU pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate incidence of ICM-induced AU cannot be acquired from reported literature since large-scale studies have grouped all HSRs (urticarial or non-urticarial, mild, or severe) caused by intra-arterially or intravenously administrated ICM together (9)(10)(11)(12). In addition, ICM-induced AU has long been regarded as non-IgE-mediated pseudoallergic reaction involving direct complement activation (13), while accumulating evidence indicated that ICM-specific IgEmediated AU (type I allergic reaction) may have been underreported in the past due to lack of pertinent allergy testing (14,15).…”
Section: Introductionmentioning
confidence: 99%